Morbidity and Mortality of Very Low Birth Weight Infants Followed in Neonatal Intensive Care Unit - Çakmak Çelik, F.; Aygün, C.; Tanyerı Bayraktar, B.; Beden, Ü.; Küçüködük, Ş.; Çetinoǧlu, E.; Aksakal, E. (My University, 2007)
In recent years survival of very low birth weight (VLBW) infants has increased by the technical and scientific developments in neonatology. However, chronic diseases like bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP) and neurological problems in surviving infants have increased. In this study, we analyzed morbidity and mortality of 297 VLBW preterm infants followed in Ondokuz Mayis University Neonatal Intensive Care Unit (NICU) between April 2003 and April 2006. Of 297 babies 71,0% survived. Respiratory distress syndrome (RDS), intraventicular hemorrhage (IVH) and necrotizing enterocolitis (NEC) were diagnosed in 36,4%, 6,4%, 6,7% of all patients respectively. Periventricular leucomalasia (PVL), BPD and ROP was diagnosed in 11,4%, 10,9%, 14,2% of surviving babies respectively. Male gender and ventilator associated pneumonia were statistically significant risk factors for BPD. Small for gestational age birth, low birth weight, tracheal intubation (TI). sepsis, patent ductus arteriosus and anemia were major risk factors for IVH. Small for gestational age birth, TI, sepsis, apnea, anemia and blood transfusion were risk factors for ROP. While bacteriemia and sepsis were main risk factors for NEC, birth at an earlier gestational age was the major risk factor for RDS. We conclude that every NICU should know its own results of morbidity and mortality for VLBW preterms and for regional organization, the results should be analyzed in succeeding years. Increasing the required equipment and caregivers in NICU may improve mortality and morbidity.
Yenidoğan Yoğun Bakım Ünitesinde İzlenen Çok Düşük Doğum Ağırlıklı Bebeklerde Morbidite Ve Mortalite
Keywords: Morbidity; Mortality; Very Low Birth Weight Baby